Change in torsional elastic constants of DNA under axial tension - Muhammad Ameer Han Rahaman (2019)
Deoxyribose-nucleic acid (DNA) is one of the most unique things that attracts researchers and scientists to study about it. It is an interesting molecule which has a geometry of that it could amazingly pack and fit its actual length of about 7 centimetres long into the cells in our bodies. Understanding the twisted molecule could open many possibilities in the future; especially in medical science and engineering.